USA's national parks - Pitts, Christopher (Lonely Planet, 2016)
Lonely Planet USA's National Parks is your passport to the most relevant, up-to-date advice on all 59 of the USA's nationally protected lands. Catch the country's 'first sunrise' from the top of Cadillac Mountain in Acadia, take the drive of your life on the Going-to-the-Sun Road in Glacier, and climb the otherworldly rocks of Joshua Tree.